Christian Influence in the Bau-Jagoi Bidayuh Traditional Funeral Customs - Yvonne Michelle, Campbell; Damien, Mikeng (Canadian Center of Science and Education, 2021)
The arrival of Christianity in the 19th century has greatly affected the traditional beliefs and customs of the Bidayuh in Sarawak, Malaysia. One of the rituals affected is that relating to funeral customs. This paper focuses on the influence of Christianity and modern lifestyle on the traditional Bidayuh funeral rites in this 21st century. The data were gathered from two funerals of traditional Bidayuh in Kampong Duyoh and Suba Baru of the Jagoi area; in Bau district. Traditional Bidayuh funeral customs are heavily influenced by their animistic beliefs and pagan/traditional rituals. Typical to any of the traditional funeral amongst the indigenous tribes of Borneo, a Bidayuh funeral is advised by a traditional priest. It is also a common trait to see it as a communal event where the whole village is involved during the wake and the funeral procession. With the conversion of most Bidayuh into Christianity, the traditional Bidayuh funeral and rites have been a rarity and exclusive only to those pagan Bidayuh. Younger generations are not exposed to the rites and tradition as funerals are in accordance to the Christian rituals. Even with the last remaining pagan Bidayuh, Christian influence could be seen in the traditional Bidayuh funeral rites and rituals.